Nursing students’ knowledge and attitudes on sexually transmitted infections prevention at training institution in Namibia - Lonia U. Hamunyela; Hileni N. Niikondo; Monika N. Nakweenda (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2024)
Background: Insufficient knowledge about sexually transmitted infections (STIs) among nursing students can impact patient care and outcomes. To address this, comprehensive STI education is crucial.